The Effect of Financial Performance on Company Quality Earnings - Indrawati, Iin; Rahmawati, Rahmawati (AKRUAL: JURNAL AKUNTANSI, 2023)
Introduction/Main Objectives: This study was conducted to provide empirical evidence of the effect of profitability, liquidity, and profit growth on the company earnings quality with leverage and firm size as the control variables. Background Problems: The Indonesia Stock Exchange (IDX) found a company that committed irregularities or discrepancies between financial statements and actual data in the technology sector. Novelty: The researcher chose a sample of the technology sector on the Indonesia Stock Exchange. Research Methods: The sample used in this study is technology sector companies listed on the Indonesia Stock Exchange during 2018-2021. Findings/Results: The results of this study indicate that profitability and liquidity has a significant positive effect on the company earnings quality, while profit growth has no effect on company earnings quality. The control variable the result obtained leverage has no effect on the company earnings quality, while firm size has a significant negative effect on company earnings quality. Conclusion: Based on the test results, it can be concluded that profitability and liquidity have a positive influence on earnings quality. Therefore, the increasing profitability and liquidity owned by the company certainly improves the quality of a company's earnings.